(untitled) (Indian Journal of Animal Production and Management, 2015)
A study was undertaken to establish time requirement for various activities involved in milking Gir, Kankrej and Crossbred cows maintained at Livestock Research Station, College of Veterinary Science and Animal Husbandry, AAU, Anand. The time taken for bringing the dam and calf from its shed to the milking parlour along with activities in the milking parlour and for taking them back from the milking parlour to its shed was recorded both during morning and evening sessions. The total time (seconds) spent / labour / adult unit / day for milking operation in crossbreds (1228.94) was higher than that recorded in Kankrej (1136.19) and Gir (1069.64) cows. This is due to higher milk yield and machine milking practiced in crossbred cows as compared to lower milk yield and hand milking followed in Kankrej and Gir cows. Variations in milking time might also be due to the intrinsic characteristics and diverse breed behavior.